Invention and intervention in African cities. - Beall, Joe (Lit, 2011)
Urban growth in Africa is higher than anywhere but, unlike earlier urbanisation trends in the industrialised world, it is not being accompanied by economic growth. The result is a continent that boasts high levels of poverty and inequality and the highest proportion of urban slum dwellers anywhere. Yet Africa has the least developed institutional architecture and infrastructure at the urban scale to effectively respond and to put in place the appropriate policy, regulatory and fiscal environment to address the social challenges of rapid urbanisation.
Keywords: Stadtforschung; Stadtwachstum; Großstadt; Stadtentwicklung; Stadtgeschichte; Verstädterung; Megastadt; Urbanisierung